Penerapan Sistem Informasi Kearsipan Dinamis dalam Pengelolaan Arsip di Kantor Arsip, Dokumentasi, dan Perpustakaan Kota Solok - Sari, Melsi Yulia; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2016)
This paper aims at: first, describe the implementation of the information chancery dynamic in the management of the archive in an office of archives, Library and documentation in Solok. Second, describe the obstacles in the system of implementation information chancery dynamic in an office of archives, Library and documentation in Solok. Third, describe their effort to face obstacles in the application ofÂ  information system chancery dynamic in the office of archives. Information are collected by observation, interviews and the literature study in the office of archives, library and documentation bookâ€™s solok. Analysis of data is undertaken on a sort of descriptive set with a qualitative approach. Based on the results of discussion can be concluded the following: First, management archive uses the information chancery dynamic that does not run well. Second, it lacksfacilities and infrastructure such as computers, scanner, servers and network and lack of human resources in the field of information technology. Third, needs for the additional facilities and infrastructure as well as the presence of socialization and training in the management of an electronic archive using information system dynamic chancery.Keyword: archive management, SIKD, electronic archive.